The trend shift caused by ecological restoration accelerates the vegetation greening of China’s drylands since the 1980s - Zidong Li; Shuai Wang; Changjia Li; Chongchong Ye; Dexin Gao; Peng Chen (Environmental Research Letters, 2022)
Satellite observations since the early 1980s have revealed a trend of ‘Earth greening’ across global terrestrial ecosystems. Dryland vegetation is more sensitive to climate change and human activities. China’s drylands are among the largest in extent worldwide, and large-scale ecological restoration of these areas has been implemented since the late 1970s, which has resulted in more complicated but still poorly quantified vegetation dynamics. To figure out the vegetation dynamics and associated driving forces, we provide an assessment of the vegetation dynamics from 1982 to 2015 using the CO _2 fertilization effect function, principal component regression, Residual Trend analysis, and Breaks For Additive Seasonal and Trend methods based on the ERA5 climate factors and GIMMS 3.1 normalized difference vegetation index datasets. This study shows that anthropogenic impacts and CO _2 fertilization have jointly led to vegetation greening in China’s drylands since the 1980s, and ecological restoration has accelerated this greening since the 2000s. The results show that the vegetation greening in China’s drylands (41.51% of the study area, +0.60 × 10 ^−3 yr ^−1 ) is mainly driven by CO _2 fertilization (+0.55 × 10 ^−3 yr ^−1 ) and anthropogenic activities (+0.12 × 10 ^−3 yr ^−1 ). The anthropogenic effects are especially higher on the Loess Plateau (+1.01 × 10 ^−3 yr ^−1 ) and the Three-North region (+0.23 × 10 ^−3 yr ^−1 ). The vegetation dynamics shifts in 6.73% (31.64 Mha) of China’s drylands were directly attributed to anthropogenic impacts around the 2000s. When the anthropogenic effect was intensified, the vegetation dynamics shifted from no change to greening and vice versa, which significantly intensified the vegetation greening since the 1980s. These results capture the processes of ecological programs and provide an assessment of the effects of ecological restoration. This work provides a credible attribution of the vegetation greenness dynamics and trend shifts in China’s drylands, thus facilitating a better understanding of regional environmental change and management.